1987
DOI: 10.1523/jneurosci.07-02-00463.1987
|View full text |Cite
|
Sign up to set email alerts
|

Brain-stem perturbations during cortically evoked rhythmical jaw movements: effects of activation of brain-stem loci on jaw muscle cycle characteristics

Abstract: The purpose of the present study was to further elucidate with the use of microstimulation techniques the influences of rostral pons and midbrain loci on the neuronal networks responsible for cortically induced rhythmical jaw movement (RJM) activity in the anesthetized guinea pig and to establish if these rostral brain-stem loci are capable of modulating the timing as well as the amplitude of rhythmical digastric (DIG) EMG activity. It was found that repetitive electrical stimulation of widespread areas of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…On comparing the location of their MRF sites inducing this suppression (cf. figure 1 of their paper) with the RJM-inducing region in the MRF found in the present study, one notes that the latter is located directly rostra1 and dorsal to the former at the level of the red nucleus, and exactly corresponds to the area from which Chandler and Tal(1987) did not obtain suppression of the CMA-induced RJM.…”
Section: Mrf Region Inducing Rja4s and Its Descending Routes Responsisupporting
confidence: 72%
See 3 more Smart Citations
“…On comparing the location of their MRF sites inducing this suppression (cf. figure 1 of their paper) with the RJM-inducing region in the MRF found in the present study, one notes that the latter is located directly rostra1 and dorsal to the former at the level of the red nucleus, and exactly corresponds to the area from which Chandler and Tal(1987) did not obtain suppression of the CMA-induced RJM.…”
Section: Mrf Region Inducing Rja4s and Its Descending Routes Responsisupporting
confidence: 72%
“…Since the MRFinduced rhythmic burst activity of the anterior digastric motoneurons persists after precollicular decerebration, as well as cerebellectomy in the paralyzed preparation with the spinal cord sectioned at the C2 level, the rhythm can reasonably be assumed to be generated in the brain stem. Chandler and Tal (1987) reported that repetitive electrical stimulation of the MRF suppressed CMA-induced RJMs in guinea pigs. On comparing the location of their MRF sites inducing this suppression (cf.…”
Section: Mrf Region Inducing Rja4s and Its Descending Routes Responsimentioning
confidence: 99%
See 2 more Smart Citations
“…6 and 7; for a review, see ref. 8) but can be modified within certain limits by the accessibility of the spout and the length of tongue travel required to reach the spout (9,10 (12,17,18). The neurons of these nuclei, the solitary nucleus, and the spinal trigeminal complex were identified as brain stem afferents to the hypoglossal nucleus (19).…”
mentioning
confidence: 99%